(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
Religion is one of the most effective intellectual guides in architecture. Thus, the Islamic religion, with its intellectual and practical dimensions, is the main effective of architectural products in form and substance. Islamic legislation represents the practical aspect. Each society has its own culture, customs and traditions. Therefore, Islamic legislation is an integrated system that governs the actions and results of this society, and that the goal of the Islamic religion and legislation is to achieve and save the five purposes: religion, self, money, supply and birth as well as justice, equality and human life reform. Architecture is one of the most effective means by which human beings achieve these goals, as well as being the most expressive of the culture of societies, which is powerful and effective in other societies, which entails religious influence in architectural design it is the general problem of research As well as the Islamic legislations derived from the Quranic texts and the noble Hadiths on the urban work which formed the special problem of the research and the study of a group of studies. The research problem was identified by: (the lack of knowledge of the impact of Islamic legislation on the crystallization of architectural products Contemporary at the level of thought and application), and the study aims to enrich knowledge about the role of Islamic legislation in the development of Arab Islamic architecture with the contents of the essence of the spirit of the age and the research adopted the descriptive analytical methodology, which includes the construction of a conceptual framework and the construction of a theoretical framework, which is the first step in solving the research problem . The most important of the research findings is (between communication and continuity, the human architecture to create creative products linked to the architecture of Islamic architecture and the ability of those products to keep up with contemporary through the realization of human needs and desires changing time and place) to conclude the research conclusions, recommendations and sources